FRI0322 Positivity for Rheumatoid Factor and Anti-Cyclic Citrullinated Peptide is Associated with A Better Drug Retention of Abatacept: Data from A Paneuropean Analysis of RA Registries. (10th June 2014) - Gottenberg, J.E.; Neto, D.; Gomez-Reino, J.; Iannone, F.; Lie, E.; Canhão, H.; Pavelka, K.; Turesson, C.; Hetland, M.; Mariette, X.; Finckh, A.
Abstract : Background: Recently, three observational studies have suggested that a positive anti-CCP status could be associated with a better response to abatacept (ABA) (1-3) and a reduction in Th1, Th2 and Th17 cytokines was reported after ABA in ACPA-positive but not in ACPA-negative patients (4). Objectives: To investigate the role of rheumatoid factor (RF) and anti-CCP positivity as predictors of ABA retention in a large observational cohort. Methods: Thisis a pooled observational database analysis of 9 European RA registries (ARTIS, ATTRA, BIOBADASER, DANBIO, GISEA, NOR-DMARD, ORA, SCQM, Reuma.PT). Inclusion criteria for this analysis were a diagnosis of RA, initiation of ABA and available information on RF and/or anti-CCP. The primary endpoint was ABA drug retention. A secondary endpoint was EULAR good or moderate response rate at one year, estimated by longitudinal interpolation and corrected for drug retention (Lundex (5)).Time to discontinuation was defined as the time between drug initiation and last administration plus one dispensation interval. Drug retention was analyzed using a Cox proportional hazards model, adjusting for potential confounders. Results: We identified 3461 pts initiating ABA (5475 pt-years (PY) of follow-up). Data on RF and anti-CCP status were available for 2409 (69.6%) and 1593 (46.0%) patients, respectively. 1781 patients were RF-positive (73.9% of those with available data), 628 (26.1%) were RF-negative. 1077 patients (67.6%)were anti-CCP-positive, 516 patients (32.4%) were anti-CCP-negative. RF positivity and anti-CCP positivity were associated with better ABA retention, with a hazard ratio (HR) (95% CI) of ABA discontinuation for any reason of 0.83 (0.73-0.94), (P=0.004) and 0.79 (0.69-0.92) (P=0.002), respectively, and for ineffectiveness of 0.70 (0.60-0.81) (P<0.001) and 0.69 (0.58-0.82) (P<0.001), respectively. The EULAR good or moderate response rates at one year tended to be higher in RF-positive than in RF-negative patients (84.1% versus 80.5%) (P=0.059) and in anti-CCP-positive patients (82.4 vs 79.7%) (P=0.22). The Lundex based on EULAR response rates were higher in RF-positive patients (60.6 versus 52.6%) and in anti-CCP-positive patients (57.0 vs 52.3%). Conclusions: Data from this Pan-European registry analysis demonstrate that positivity for RF and anti-CCP are associated with better ABA retention. This association was consistently observed across the European registries contributing to this pooled analysis and confirms the results of 3 smaller studies. The mechanisms underlying the association remain to be elucidated. References: Gottenberg et al. ARD 2012. Nüßlein H et al. EULAR 2013, abstract 106. Sekiguchi M, et al, ACR 2013, abstract 465. Pieper et al. BMC Immunol 2013. Kristensen LE. et al. Arthritis Rheum 2006. Disclosure of Interest: J. E. Gottenberg: None declared, D. Neto Grant/research support: unrestricted research grant from BMS, J. Gomez-Reino: None declared, F. Iannone: None declared, E. Lie: None declared, H. Canhão: None declared, K. Pavelka: None declared, C. Turesson: None declared, M. Hetland: None declared, X. Mariette: None declared, A. Finckh Grant/research support: unrestricted research grant from BMS DOI: 10.1136/annrheumdis-2014-eular.5345